The Effect of Turmeric (Curcuma Domestica Val.) Extract on the Histopathological Lesions of Lung Induced by Cigarette Smokes in Wistar Rats - laelatul Rahmad; Nida Ul Milah; Agapietta Kusumawardani; Novi Herliyani; Kurniati Sarwendah; Bambang Sutrisno; Hastari Wuryastuti; R Wasito (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
This present study is aimed to observe and determine the effects of turmeric (Curcuma domestica Val.) extract administration towards the cytotoxicity effect of cigarette smokes in the lungs of Wistar rats. Twenty Wistar rats, male, 3 months old, were used and divided randomly into four groups, of five each. Group I is as a control (K I), Group II was given 9 cigarettes/day without turmeric extract administration (K II), Group III giventurmeric extract 1 ml 0.25%/day (K III) and Group IV was given 9 cigarettes/day and turmeric extract 0.25%/day (K IV) for 60 days. At the end of the present study, all rats were necropsied and organs, particularly the lungs were collected, processed histopatologically and stained routenely with hematoxilyn eosin. The results indicated that the lungs had macrophages infiltration in the septal alveoli and hyperplasia of bronchial associated lymphoidtissue (K II). Whereas, the lungs in the rats in Groups K I, K III and K IV were still within the normal limits. It is concluded, that turmeric extract may have a potential antipulmonary cytotoxity effect due to cigarette smoke.